Shared decision-making and the caregiver experience in tuberous sclerosis complex: results from a UK survey - Hanna Skrobanski; Kishan Vyas; Sally Bowditch; Lena Hubig; Edward Dziadulewicz; Louise Fish; Pooja Takhar; Siu Hing Lo (Orphanet Journal of Rare Diseases, 2023)
Abstract Background Tuberous sclerosis complex (TSC) is a rare genetic condition commonly accompanied by neurological and neuropsychological disorders, resulting in a high burden of illness for individuals and a substantial impact on their caregivers. Due to the diversity and complexity of clinical manifestations, patients with TSC need aligned multidisciplinary healthcare services starting in childhood through to adulthood. However, patients and caregivers are sometimes dissatisfied with the care provided, for which one of the most common reasons is a lack of involvement in clinical decision-making. Shared decision-making, whereby clinicians make clinical management decisions together with patients and their caregivers, is advocated for in the management of epilepsy, but evidence of its benefit in managing TSC is currently lacking. In this cross-sectional, UK-based analysis we used an online survey to capture the experiences of primary caregivers for individuals with TSC, including the impact on work productivity, clinical shared decision-making, satisfaction with care, and the impact of the coronavirus disease 2019 (COVID-19) pandemic. Results In total, 73 eligible caregivers provided consent (analysis set), with 14 completing the survey partially and 59 completing the full survey. Many caregivers (72%) reported receiving recommendations about new treatments from their doctor and discussing the treatment together, with a high proportion (89%) preferring that treatment was initiated at a low dose. Most caregivers (69%) were satisfied or extremely satisfied with pediatric TSC healthcare services, but only 25% were satisfied or extremely satisfied with the transition to adult TSC healthcare services. Several (n = 30) caregivers specified the impact of caring on their work productivity and career in optional open-ended survey responses. Finally, 80% of caregivers indicated that the COVID-19 pandemic had a “large” or “very large” impact on their caring activities, negatively affecting the emotional wellbeing and behavior of individuals with TSC, and caregivers’ ability to work and arrange medical appointments. Conclusions Caregivers largely feel involved in treatment decisions, and the majority were satisfied with healthcare services for children with TSC. However, many highlighted the need for an improved transition from pediatric to adult healthcare services. The survey also showed that COVID-19 has considerably affected caregivers and individuals with TSC.